(untitled) (ENTHYMEMA, 2014)
Questo articolo esamina l’intreccio di identità e scrittura nel romanzo nabokoviano The Real Life of Sebastian Knight (1941) da una prospettiva psicoanalitica, seguendo in particolare l’insegnamento di Freud e Lacan sul concetto di desiderio, significante e sublimazione artistica. L’attenzione principale sarà dedicata al rapporto tra i fratellastri, V. (il narratore) e Sebastian. Dopo aver dimostrato che Sebastian Knight ha assunto il ruolo di oggetto del desiderio per chi lo ha conosciuto intimamente (soprattutto V.), muovendo i personaggi secondo ciascun modo d’essere, si passerà al trauma della sua morte e all’elaborazione del lutto da parte del narratore, grazie alla creazione letteraria (la biografia fittizia che leggiamo); il paragrafo conclusivo analizza i cosiddetti ’inganni’ del significante, episodi chiave in cui il narratore prende contatto con la verità del desiderio. Dato l’ineludibile interrogativo sulla paternità fittizia della Real Life (se l’autore fosse Sebastian Knight?) e la questione del ’tocco artistico’ di V., in questa argomentazione non verranno trascurati gli aspetti metaletterari dell’opera. This paper examines, from a psychoanalytic standpoint, the intersection between identity and writing in the novel The Real Life of Sebastian Knight (1941) by Vladimir Nabokov. In particular, in the wake of Freud and Lacan, the following contribution will take the notions of desire, signifier, and the process of sublimation involved in artistic creation as interpretative devices. The main focus of the analysis will be the relationship between the two half-brothers of the novel, V (the narrator) and Sebastian. First, I will show that Sebastian Knight holds the role of the object of desire for the characters who have established a close relationship with him and, in particular, for V. Secondly, the paper will be devoted to the analysis of the trauma experienced by the characters because of Sebastian’s death, with a particular focus on the narrator’s mourning through writing (the fictional biography we read in the novel); in the end, I will give evidence of the so-called signifier’s fallacy, crucial episodes in which the narrator can experience an insight into the truth of desire. Because of the not negligible question of the fictional paternity of The Real Life and the equally essential matter of V’s ‘stylistic touch’, metaliterary aspects of the novel will also be part of the following reading of the text.